2019
DOI: 10.1371/journal.pone.0224895
|View full text |Cite
|
Sign up to set email alerts
|

Head to head comparison of two commercial fecal calprotectin kits as predictor of Mayo endoscopic sub-score and mucosal TNF expression in ulcerative colitis

Abstract: BackgroundFecal calprotectin is widely used to monitor disease activity in patients with inflammatory bowel disease. Multiple commercial kits exist, however, since the analyses are not standardized, these kits cannot be used interchangeably. We aimed to perform a technical evaluation of two kits (Calpro from Calprolab, Norway and Calprest from Eurospital, Italy) and perform a tuning for detection of clinically relevant disease states in ulcerative colitis.Materials and methodsFor tuning against different clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These results are in agreement with prior studies in which Labaere et al, reported that Quantum blue’s FC results values were higher (up to 5 times) than those of ELISA or other immunochromatography assays, and Jang et al, reported low specificity (40%) of Buhlmann Quantum Blue assay in discriminating IBD from other colitis groups[ 11 , 12 ]. The findings of the present study confirm that it is inappropriate to directly compare absolute calprotectin levels between different kits and it is necessary of kit-specific cut-off level [ 6 ]. This highlights the need for standardization of FC levels.…”
Section: Discussionsupporting
confidence: 58%
“…These results are in agreement with prior studies in which Labaere et al, reported that Quantum blue’s FC results values were higher (up to 5 times) than those of ELISA or other immunochromatography assays, and Jang et al, reported low specificity (40%) of Buhlmann Quantum Blue assay in discriminating IBD from other colitis groups[ 11 , 12 ]. The findings of the present study confirm that it is inappropriate to directly compare absolute calprotectin levels between different kits and it is necessary of kit-specific cut-off level [ 6 ]. This highlights the need for standardization of FC levels.…”
Section: Discussionsupporting
confidence: 58%
“…Most studies except 3 studies [15-17] used a prospective study design. Seven of the studies were conducted in Asia (4 studies in Japan [8, 9, 11, 18], 3 studies in Korea [17, 19, 20]), 6 of the studies were in Europe (1 in Belgium [21], 3 in Norway [22-24], 2 in Denmark [15, 25]), 1 of the studies was in Canada [10], 2 of the studies were in the USA [16, 26], 1 of the studies was in Australia [27], and 3 of the studies were multicenter [28-30]. Reference standards of most included studies were based on endoscopy, including MES, UCEIS in MH evaluation of UC, and SES-CD in MH evaluation of CD.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated 1 FC level cut-off range (180–250 μg/g) in CD as per availability of reports in the included studies. When MH was defined as MES 0, 4 studies [15, 24, 28, 30] (MH was based on histologic activity evaluation in 1 study[25]) about FC with cut-off range of 25–50 μg/g, 5 studies [16, 20, 22, 28, 30] about FC with cut-off range of 60–75 μg/g, 4 studies [20, 22, 24, 28] about FC with cut-off range of 96–125 μg/g, 5 studies [11, 17, 19, 28, 30] about FC with cutoff range of 150–180 μg/g, and 6 studies [8, 15, 19, 26, 28, 29] about FC with cut-off range of 192–201 μg/g for predicting MH in UC patients were included in the final meta-analysis (Table 1). When MH was defined as MES 0–1 or UCEIS 0–1, 4 studies [17, 26, 28, 29] (MH was based on histologic activity evaluation in 1 study [26]) about FC with cut-off range of 170–200 μg/g and 6 studies [8, 21-23, 26, 28] about FC with cut-off range of 250–259 μg/g for predicting MH in UC patients were included in the final meta-analysis (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…When we compare our results with similar studies, we see that other authors got comparable results. Goll et al in their study found good correlation between assays, however a non-linear difference was found: at values below 200 mg/kg, no significant bias was found; in the interval 200 - 1000 mg/kg the Calprest assay measured on average 30% lower than Calpro; and at higher values Calprest measured 60% higher values than Calpro ( 22 ). Haisma et al evaluated by how much different tests differed from the trusted ELISA method, and found that in the lower ranges the difference was small enough not to cause problems in interpretation.…”
Section: Discussionmentioning
confidence: 92%